Adaptability Analysis for Sand Proppant to Conglomerate Oil Reservoir in Well-block MA 131 of Xinjiang Oil Field. Issue 1 (May 2021) - Chen, Ang; Zhang, Zhao; Tang, Wei; Wang, Lei; Yu, Huiyong
Abstract: SRV (Simulated Reservoir Volume) in horizontal well is a main instrument for exploiting dense conglomerate oil reservoir in Ma Lake. The expenses of proppant are about 25% to 30% of the total SRV costs. In order to reduce costs and improve efficiency, it is inevitable to replace ceramic proppant with quartz sand, because the price of quartz sand is significantly lower than ceramic proppant. With Well-block Ma 131 as an object, this paper analyzes post-SRV production result of the existing alternative sand well; creates simple fracture and curved fracture model based on features of conglomerate oil reservoir; plots required conductivity of the target area through simulation and calculation; and analyzes adaptability of sand proppant to the target area based on conductivity data of sand proppant. The results indicate that the required conductivity of Well-block Ma 131 changes within 10 and 35 D·cm; quartz sand can accommodate production demands completely when closure pressure is low; and required conductivity can be realized through improving sanding concentration when the closure stress is high.